A Meta-Analysis of the Literature on Agricultural Innovation - Sharma, Haridra (International Journal of Bio-resource and Stress Management, 2019)
Agricultural technologies are being innovated and evaluated to assess its impact on agriculture. The findings of such evaluative studies are being published in different forums for the benefit of mankind. As such, a huge literature has emerged in recent years revealing different methodologies and approaches of evaluation. The purpose of the present study is to find out ways the innovations in agriculture are being evaluated, through a meta-analysis of 25 systematically selected articles. The specific objectives are to identify the variables explaining agricultural innovation and to analyze the relationship among those variables. The results revealed that majority of the literature discussed the innovation with prime purpose – ‘environment protection (60%)’, followed by ‘improving farm performance (28%)’. The main agricultural innovations studied by researchers are those processes which involve the ‘environment preserving technologies (36%)’ and ‘precision technologies (20%)’. Evaluation indicators such as the ability to ‘reducing environmental impact (32%)’ and ‘strengthening farmer’s participation (32%)’ were studies in most of the cases. In terms of innovation strategies, both proactive (44%) and reactive (48%) approach were found almost equally. On analysing the relationship between the identified categorical variables, it came to the knowledge that studies focusing on environment protection as prime purpose included the analysis of innovation processes related to environment preserving and precision technologies that are capable of reducing environmental impact through strengthening farmer’s participation and are proactive in nature.